THE INFLUENCE OF PRICE ON INSTO COOL PRODUCT PURCHASE DECISIONS AT PT PHARMA HEALTH CARE JAKARTA - Agus Suhaila, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The economy is growing rapidly, leading to intense competition in all areas of life. One example of competition in the eye drop industry is the presence of Cool Eye Drops. The wide variety of eye drop products available on the market at various price points can influence consumer purchasing decisions. Consumer purchasing decisions are an important factor in determining the existence of a company. When making purchasing decisions, the first thing consumers usually consider when choosing a product is the price of the product. The sampling technique in this study used validity testing with factor analysis, reliability testing with the Cronbach's alpha method, correlation coefficient testing, determination coefficient testing, and simple linear regression testing. The test and analysis results in this study prove that the correlation coefficient value is 0.838 and the coefficient of determination value is 0.702. then the simple linear regression value of the price variable is positive, it is known that the price constant value is 0.932 units of the price variable will affect the purchase decision by 0.932, assuming that other variables are not studied in this research.